Chemical Composition, pH Value, and Points of Zero Charge of High Calcium and High Iron Electric Arc Furnace Slag - Zu Nurain Ahmad, Siti; R, Hamdan; Afnizan Wan Mohamed, Wan; Othman, N; Shaylinda Mohd Zin, Nur (International Journal of Engineering and Technology, 2018)
Electric arc furnace (EAF) slag as filter media has been extensively used nowadays for wastewater treatment technology. Steel slag was produced as byproduct from steelmaking processes. However, different batches of steel slag production produce different composition. Thus, this study determined the chemical composition, pH value and points of zero charge (PZC) of two different samples of electric arc furnace (EAF) slag; high iron EAF slag (Slag HFe) and high calcium EAF slag (Slag HCa). The steel slag were characterized using X-ray Fluorescence Spectroscopy (XRF) analysis for the chemical composition, extraction with boiling water for pH value, and salt addition method for PZC. Slag HFe was mainly consisted of 38.2% ferric oxide and 20.4% calcium oxide, 10.20 pH value and pH 10.55 for PZC. While for Slag HCa, they were composed of 1.64% ferric oxide and 49.5% calcium oxide of pH value of 11.11 and pH 11.75 for PZC. Therefore, Slag HCa was considered as a more basic species compared to Slag HFe.Â